Dyslipidaemia among Ghanaian migrants in three European countries and their compatriots in rural and urban Ghana: The RODAM study. (May 2019) - van der Linden, Eva; Meeks, Karlijn; Beune, Erik; de-Graft Aikins, Ama; Addo, Juliet; Owusu-Dabo, Ellis; Mockenhaupt, Frank P.; Bahendeka, Silver; Danquah, Ina; Schulze, Matthias B.; Spranger, Joachim; Klipstein-Grobusch, Kerstin; et al.
Abstract: Background and aims: African populations have a favourable lipid profile compared to European populations. However, the extent to which they differ between rural and urban settings in Africa and upon migration to Europe is unknown. We assessed the lipid profiles of Ghanaians living in rural- and urban-Ghana and Ghanaian migrants living in three European countries. Methods: We used data from a multi-centre, cross-sectional study among Ghanaian adults residing in rural- and urban-Ghana and London, Amsterdam and Berlin (n = 5482). Dyslipidaemias were defined using the 2012 European Guidelines on Cardiovascular Prevention. Comparisons between groups were made using age-standardised prevalence and prevalence ratios (PRs) with adjustments for important covariates. Results: In both sexes, the age-standardised prevalence of high total cholesterol (TC) and LDL-cholesterol (LDL-C) was lower in rural- than in urban-Ghana and Ghanaian migrants in Europe. Adjusted PRs of high TC and LDL-C were higher in urban-Ghana (TC PR = 2.15, 95%confidence interval 1.69–2.73) and Ghanaian migrant men (TC PR = 2.03 (1.56–2.63)) compared to rural-Ghana, but there was no difference between rural- and Ghanaian migrant women (TC PR = 1.01 (0.84–1.22)). High triglycerides levels were as prevalent in rural-Ghana (11.6%) as in urban-Ghana (12.8%), but were less prevalent in Ghanaian migrant women (2.0%). In both sexes, low HDL-cholesterol was most prevalent in rural-Ghana (50.1%) and least prevalent in Europe (12.9%). Conclusion: The lipid profile varied among ethnically homogeneous African populations living in different geographical locations in Africa and Europe. Additional research is needed to identify factors driving these differential risks to assist prevention efforts. Graphical abstract: Image 1 Highlights: Total cholesterol and LDL-C rates were similar for men in urban Ghana and Europe. High total cholesterol and LDL-C were most prevalent in urban Ghanaian women. High triglycerides were more prevalent in Ghanaian women in Ghana than in Europe. Low HDL-C was most prevalent in rural Ghana, followed by urban Ghana and Europe. TC/HDL-C-ratio was the highest in urban Ghanaian men and women.